De' Moment Arts Photography - Osman, Fadlillah; Masri, Mohd Ashreeq; Abdul ghani, Mohd Rizaizy; Ag Delin, Iranisah (2013)
De' Moment Arts Photography is a business of photography and the business will start on the end of 2014. Services that will be provided are Studio Portraiture, Outside the studio Portraiture, Wedding, Non - Commercial Event, Commercial Event, Protocol Event, and more else that are related to this service. This business location is located at Al Mubarak Masjid Bandaraya Likas. This location is situated in the mosque of Kota Kinabalu. Therefore, it will have a great potential market for this business. This year economic situation is stable, therefore we expect that in 2020, Malaysia economic will continue and achieve their growth target. As the country prosper, more people are employed, making standard living of people in Malaysia and getting better each year. Furthermore, our ways of thinking has changed people mind that, every time we need to capture a photograph for a memory as our age is growing older. We believe that our business have potential in this millennium especially in urban area because people are always looking for a better service at this area. Moreover, the population and growth of people are getting higher and for sure they will plan for a marriage and any event. Another factors that influencing us to choose this photography service is because in Kota Kinabalu, every weeks there are many event and marriage happen and it make it easier for us as a new entrepreneur to engage in the business.